Evaluation of Optima Regional Health Information System with HOT-Fit on Technology Aspects Approach in Johar Baru Health Center Jakarta - Ahmad Fauzan; Noviandi Noviandi (Universitas Muhammadiyah Semarang Press, 2020)
The Information technology development has affected various sectors, including health services. The several technologies have been used to improve health facilities performance. At Johar Baru Health center, central Jakarta, SIKDA (Sisitem Informasi Kesehatan Daerah) Optima application has been applied. Meanwhile, the implementation of SIKDA Optima is not as good as expected. There still many disruptions during the use of this application such a delay service and delivery of report was not in a real time, therefore an evaluation is needed. The purpose of this study was to determine the quality of system, information, and service which is affecting the satisfaction of SIKDA Optima users at Johar Baru Health Center, Central Jakarta. This study used a quantitative approach with observational survey and cross-sectional design. The population in this study was 98 persons and the sample were 79 users of SIKDA Optima, consist of 19 doctors, 22 nurses, 17 midwives, 9 pharmacies, 2 medical recorder and 10 administration staffs. Data analysis was performed using multiple linear regression. The results of multiple linear regression test showed that the user satisfaction of SIKDA Optima = -3.832 + 0.549 (KS) + 0.757 (KI) + 0.359 (KL) with a p-value of KS 0.001<0.05), p-value KI 0,000 <0,05), and the p-value of KL is 0.009 <0.05. The conclusion of this study is the quality of system, information, and services that is used at Johar Baru Health Center have a significant influence on the satisfaction of SIKDA Optima users.